Traumatic perforations are associated with previous tympanostomy tube placement. (September 2021) - Isaacson, Glenn; Reilly, Brian
Abstract: Introduction: Recognized late complications of tympanostomy tube placement include persistent tympanic perforation, tympanosclerosis, and focal atrophy. Based on clinical experience, we suspected that atrophy at healed tympanostomy tube sites might predispose to re-perforation following trauma. Methods: Computerized record review of children seen in an academic pediatric otolaryngology practice from January 2001 to December 2020. Results: 33 children with confirmed traumatic tympanic perforations and complete follow-up were identified. All perforations were unilateral. 19 of 33 (58%) perforations were in children with tympanostomy tube placement in the past and 14/33 (42%) had never had tubes. 17/19 (90%) traumatic perforations in the tube group were due to blunt or barotrauma rather than penetrating trauma as compared with 6/13 (46%) in the non-tube group (p = 0.0147 by Fisher's exact test). One patient in the non-tube group had an unknown mechanism of injury. 15/19 perforations in the tube groups were in the antero-inferior or antero-superior quadrants (old tube sites) compared to 4/14 in the non-tube group (p = 0.0152). Perforations tended to be larger in the non-tube group (non-tube mean perforation size = 27%/tube group mean = 18%) The median time to re-perforation was 8 years (range 3–15 years). Boys predominated in both perforation groups. Conclusion: Traumatic perforations in this series occurred more often in the antero-inferior quadrant (old tube site) in children with previous tympanostomy tube placement. These perforations tended to be smaller and less often resulted from penetrating injuries than in children who had never undergone tube placement. Level of evidence: 3B – individual case-control study.